2008
DOI: 10.2147/vhrm.2008.04.01.157
|View full text |Cite
|
Sign up to set email alerts
|

Adherence treatment factors in hypertensive African American women

Abstract: Background: Hypertension among African American women is of epidemic proportions. Nonadherence to treatment contributes to uncontrolled blood pressure in this population. Factors associated with adherence to treatment in African American women are unknown. The purpose of this study was to identify factors associated with adherence to hypertension treatment in African American women. Methods: Five audio-taped focus groups were conducted with hypertensive African American women, 35 years and older receiving trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
42
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 32 publications
(37 reference statements)
7
42
1
Order By: Relevance
“…In some studies, hypertensive African–Americans reported that social support helped them to remain adherent to antihypertensives [18,22,24,25]. However, others report that social support is not associated with medication adherence in hypertensive African–Americans [21,26,27].…”
Section: Patient and Clinical Factors Associated With Medication Adherementioning
confidence: 99%
See 1 more Smart Citation
“…In some studies, hypertensive African–Americans reported that social support helped them to remain adherent to antihypertensives [18,22,24,25]. However, others report that social support is not associated with medication adherence in hypertensive African–Americans [21,26,27].…”
Section: Patient and Clinical Factors Associated With Medication Adherementioning
confidence: 99%
“…Clinical encounters with healthcare providers are important to patients [22,24,25,34]. The authors examined three studies reporting that African–American hypertensive patients who perceived their provider communication as empathetic, and collaborative were more likely to adhere to their antihypertensive medication regimen [27,30,35].…”
Section: Provider and Healthcare System Correlates Of Medication Adherementioning
confidence: 99%
“…12 These disparities may be mediated, in part, by patients’ beliefs and attitudes towards disease and treatment. 17 This has been established for other health conditions—notably, high blood pressure treatment adherence, 18,19 HIV therapy adherence, 20,21 utilization of health services, 22 and colorectal cancer screening. 23 Few studies have investigated patients’ perception about sleep apnea evaluation and treatment specifically in blacks, a population at great risk for OSA and related medical and psychosocial conditions.…”
Section: Introductionmentioning
confidence: 99%
“…However, while research studies [16][17][18][19][20] have been conducted on adherence issues in hypertensive African Americans, none have used perceived freedom of choice as the mediator of health behaviors in relation to HTN.…”
Section: Factors Affecting Adherencementioning
confidence: 99%
“…2 Nevertheless, about 50% of patients with HTN do not adhere to the treatment regimen. 5,41 Factors related to nonadherence to the antihypertensive health regimen in African Americans include historical, socioeconomic, cultural, and physiological determinants such as the need to cope with multiple stressors, divergent health beliefs, medication side effects/adverse reactions, inadequate lifestyle modifications, 42 poor social support, alcohol and illicit drug use, cost factors, lack of health insurance, lack of access to care, 19 cultural traditions for diet and food preparation, 43 perceived racism, lower socioeconomic status, distrust of health care providers, low literacy, and poor communications with health care providers. 44 Because untreated or poorly managed HTN can result in death from heart failure, kidney disease, stroke, or coronary heart disease, 1,2,4 it may be difficult for health care providers to understand why an individual with HTN chooses not to adhere to the regimen, especially if ample resources are available and other factors known to affect adherence are not involved.…”
Section: Resourcesmentioning
confidence: 99%